2020
DOI: 10.1039/c9cp06453b
|View full text |Cite
|
Sign up to set email alerts
|

DFT insights into electrocatalytic CO2 reduction to methanol on α-Fe2O3(0001) surfaces

Abstract: Electrocatalytic reduction of CO2 to manufacture fuels and other useful chemicals is one of the appealing methods to reuse CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Among thousands of possible reaction pathways, the key steps are CO formation and C-C coupling. Typically, the first CO 2 reduction reaction step is the hydrogenation of CO 2 , which results in the generation of formate (*HCOO) or carboxyl (*COOH) (Kumar et al 2020). Subsequently, CO would be formed from *COOH, and further reduced to other carbon-based fuels.…”
Section: Intermediates and Reaction Pathwaysmentioning
confidence: 99%
“…Among thousands of possible reaction pathways, the key steps are CO formation and C-C coupling. Typically, the first CO 2 reduction reaction step is the hydrogenation of CO 2 , which results in the generation of formate (*HCOO) or carboxyl (*COOH) (Kumar et al 2020). Subsequently, CO would be formed from *COOH, and further reduced to other carbon-based fuels.…”
Section: Intermediates and Reaction Pathwaysmentioning
confidence: 99%
“…Several types of 2D MXene materials with M 2 X, M 3 X 2 , and M 4 X 3 stoichiometry have been synthesized using fluorine and hydrogen from precursor MAX phases and found to exhibit large surface areas in the range of 250–1000 m 2 g –1 . Interestingly, MXenes possess high adsorption energies when compared to other 2D materials, as shown in Figure . Zhang et al studied O surface-functionalized MXene Ti 2 C (Ti 2 CO 2 ) and found enhanced photocatalytic performance for CO 2 reduction to formic acid. Later, Li et al theoretically observed M 3 C 2 -type (Mo 3 C 2 and Cr 3 C 2 ) MXenes as most promising candidates for CO 2 conversion into hydrocarbon fuels …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption energies of CO 2 on various 2D materials collected from literature. The purple balls correspond to MXenes (M 2 C, M 3 C 2 , and M 4 C 3 (M = Ti, V, Zr, Nb, and Mo) and orange balls represent other 2D materials such as Cu 2 O, MoS 2 , MoSe 2 , WTe 2 , WSe 2 , MgO, In 2 O 3 , Fe 2 O 3 , ZnO, SnO 2 , GaN, Ga 2 O 3 , and X-AlC (X = B, N, P, Si). This analysis clearly indicates that the E ads of CO 2 on MXenes are highly negative when compared to other 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, DFT-based calculations have been found to be useful in predicting various mechanisms of the ERC using modeled surfaces. [127,128] The DFT-based calculations are equally applicable both for predicting the product selectivity as well as the mechanistic insights in the case of Cu electrocatalysts. Hussain et al [129] obtained calculated reaction rates using combined DFT and rate theory, and compared their results with the experimental findings.…”
Section: Theoretical Investigations On Cu-based Electrodesmentioning
confidence: 99%